(untitled) (LACCEI, 2024)
The present study aimed to analyze the development of software with educational accessibility in the last ten years, oriented to each type of disability, sources of publication, country and year of study, target educational level, types of software and tools used for its development and database management. To this end, a systematic review was developed with inclusion and exclusion criteria, with the methodology adapted from PRISMA. We selected 35 studies that met the inclusion criteria. As the most relevant results and conclusions, it was obtained that the largest number of studies come from Ecuador with a significant advantage over other countries. The disabilities with the greatest attention were intellectual or cognitive disability (33%), followed by visual impairment (31%) and hearing impairment (17%), which require greater attention and support in learning. The educational level with the highest development was the primary level, for children with disabilities (73%). The educational areas with the greatest reach were communication (37%) and training of learning skills and abilities (26%). The type of software that stood out was the web application (23%), followed by the mobile application (17%). The most used development tools were SDK, LabVIEW and Python, and MySQL, SQLite for database management.